Work engagement as a mediator of transactional leadership and workload on employee turnover intention - Hesty Rahmadani; Ilzar Daud; Yulyanti Fahruna; Titik Rosnani; Anwar Azazi (Institute of Computer Science (IOCS), 2023)
Applying replacement value of goods and salary deductions as sanctions is part of the transactional leadership policy. This burdens employees, which makes them choose to leave their jobs. Therefore, work engagement is expected to mitigate this. This study investigates the impact of transactional leadership and workload on turnover intention, considering work engagement as a mediator. The population in this study were permanent employees of PT Sumber Alfaria Trijaya Tbk Alfamart Retail Business Division in Kalimantan, with a sample size of 205 respondents. Data collection methods using a questionnaire with a Likert scale. The data analysis model uses Structural Equation Modeling (SEM) and AMOS 24 statistical tools. The results of this study indicate a significant positive influence between transactional leadership and workload on turnover intention. Transactional leadership and workload variables also significantly positively affect work engagement. The mediation analysis results show the role of work engagement as a mediator in strengthening the relationship between transactional leadership and workload on turnover intention. This research is expected to prevent the increasing turnover in the retail business company PT Sumber Alfaria Trijaya Tbk (Minimarket Alfamart).